Distributions of Sr and Fe and their influence on modification of hypoeutectic Al-Si alloy - Tu Lan (China Foundry, 2016)
The influence of cooling rate and Fe-containing phases on Sr-modification of Si phases in hypoeutectic Al-Si alloys, a problem with great industrial importance, was investigated. The microstructures of samples were examined using scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX). A new method of electron probe microanalysis (EPMA) map scanning was used to analyze the Sr distribution, which gave quantitative results covering more Si particles. EPMA map scanning, together with SEM with EDX, was also used in analyzing the distribution of Fe phases. Results show that Fe-containing phase was related to the unmodified Si particles in samples with partial modification failure and the plate-like Si phases in samples without modification failure. Such a relationship was further confirmed by the microstructure observation. In conclusion, a partial failure of Sr-modification can be caused by both slow cooling rate and Fe-containing phases.